Acute renal failure associated with the new BRAF inhibitor vemurafenib: A case series of 8 patients. Issue 14 (15th April 2014) - Launay‐Vacher, Vincent; Zimner‐Rapuch, Sarah; Poulalhon, Nicolas; Fraisse, Thibault; Garrigue, Valérie; Gosselin, Morgane; Amet, Sabine; Janus, Nicolas; Deray, Gilbert
<x xml:space="preserve">Abstract</x> BACKGROUND Vemurafenib is a BRAF inhibitor that has become the cornerstone of metastatic or inoperable melanoma therapy since its approval in 2011 in the United States and 2012 in Europe. This targeted therapy has shown impressive results in terms of increased progression‐free and overall survival as compared to dacarbazine. The safety profile did not include any renal manifestations at that time. METHODS This report is the first case series of 8 patients who experienced significant to severe renal insufficiency under vemurafenib treatment. RESULTS This case series shows that vemurafenib may induce potentially severe acute renal failure, including renal sequelae and persistent kidney disease in some cases. CONCLUSIONS Further studies are needed to investigate the effects of vemurafenib on the kidneys. Meanwhile, renal function should be closely monitored in treated patients for early detection of any renal dysfunction occurrence. Cancer 2014;120:2158–2163. © 2014 American Cancer Society.